Association of oral health knowledge, attitudes, and practice with dental caries status among 6–12-year-old Iranian orphaned children using the CAST index: A Cross-sectional study - Zahra Jahanbakhti; Zahra Momeni (PLoS ONE, 2026)
Introduction Orphaned children face heightened vulnerability due to the absence of parental care and limited access to preventive services. Evidence linking oral health knowledge, attitudes, and practice (KAP) with clinical outcomes in this population remains limited. This study aimed to assess oral health KAP among orphaned children in Karaj, Iran, and examine their associations with clinical indicators of dental caries, gingival status, and oral hygiene. Methods In this cross-sectional study, 72 children aged 6–12 years residing in four government-run quasi-family centers in Karaj were examined between October 2024 and January 2025 through a census sampling approach. Inclusion required age eligibility and informed consent, whereas children with systemic or developmental disorders or those receiving orthodontic treatment were excluded. Data were collected using a structured, validated questionnaire (α = 0.83) to assess KAP and demographic factors. Clinical examinations were performed by a calibrated examiner (ZJ) (Kappa = 87.68%) using the CAST, GI, and OHI-s indices. Logistic and linear regression models were used to examine predictor variables of KAP and oral health outcomes. Results The mean scores of knowledge, attitude, and practice were 3.16 ± 1.60 (out of 7), 33.52 ± 4.36 (out of 50), and 10.26 ± 2.72 (out of 20), respectively. Overall, 62.5% of children demonstrated fair oral hygiene (OHI-s = 1.75 ± 1.58) with mild gingival inflammation. CAST assessment indicated that fewer than one-third of primary molars were sound, while more than half of permanent first molars showed enamel caries. Regression analyses showed that frequent toothbrushing (p = 0.015, OR=0.52, 95% CI: 0.30–0.88) and more positive attitudes toward oral health (p = 0.013, OR=0.70, 95% CI: 0.53–0.93) were significant predictors of improved oral status, whereas knowledge and self-reported practice were not consistent predictors. Conclusions Orphaned children in Karaj demonstrated moderate oral hygiene, a high prevalence of untreated dental caries, and limited awareness of oral health. Addressing these behavioral and systemic gaps through targeted, evidence-based interventions—particularly oral health education, caregiver involvement, and routine dental monitoring—may help improve oral health outcomes in this vulnerable population.